Naphthalenones and Isocoumarins from a Costa Rican Fungus Xylariaceae sp. CR1546C - Kim, Ki Hyun (2014)
A new naphthalenone, (R)-4,6,8-trihydroxy-3,4-dihydro-1(2H)-naphthalenone and a new isocoumarin, 6,8-dihydroxy-(3R)-(2-oxopropyl)-3,4-dihydroisocoumarin, together with eight related known compounds were isolated from the endolichenic fungal species, CR1546C from Costa Rican lichen Sticta fuliginosa (Lobariaceae). Their structures were elucidated by spectroscopic methods, including extensive 1D- and 2D-NMR techniques and chemical methods. All of the isolated compounds exhibited moderate antifungal activity against the yeast Candida albicans.